1989
DOI: 10.1212/wnl.39.7.897
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic basal ganglia hemorrhage

Abstract: Traumatic basal ganglia hemorrhage (TBGH) is probably secondary to rupture of lenticulostriate or anterior choroidal arteries. We evaluated 6 consecutive cases of this entity to define its clinical and pathologic dimensions. Relative frequency of TBGH was 3% (3 left, 3 right) in this acute rehabilitation population. Lesion size and associated pathology varied. Contralateral hemiparesis, present in all, recovered to varying extents, apparently related to lesion location (posterior limb, internal capsule, or mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 0 publications
0
79
1
1
Order By: Relevance
“…9,16) Axonal injury is occasionally associated with perforating branch injury, resulting in hemorrhage or infarction due to shearing force. 1,12) Therefore, shearing force to the paramedian branch of the basilar artery may have caused the cerebral infarction in this case.…”
Section: Discussionmentioning
confidence: 80%
“…9,16) Axonal injury is occasionally associated with perforating branch injury, resulting in hemorrhage or infarction due to shearing force. 1,12) Therefore, shearing force to the paramedian branch of the basilar artery may have caused the cerebral infarction in this case.…”
Section: Discussionmentioning
confidence: 80%
“…Mosberg and Lindenberg, 4 in an autopsy of fatal head injury patient, demonstrated massive hematoma in the improvement in all patients managed conservatively. Kimura et al, 13 Katz et al, 3 and Jang et al 7 have also reported favorable outcomes for TBGH with conservative management. Surgical evacuation entails approach to the hematoma via the thalamoganglionic region, leading to further damage of the eloquent areas resulting in possible poor outcome.…”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3] The patients with TBGH have increased incidence of coagulation abnormalities, diffuse axonal injury, intraventricular hemorrhage, and intra-/extraaxial bleed and have a correspondingly poor outcome. Since basal ganglia region is predisposed to hypertensive bleed, at times, it becomes difficult to distinguish between hypertensive and traumatic hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6,[10][11][12] The exact pathogenesis of TBGH is not clear, but, it has been suggested that the TBGH can occur from acceleration/deceleration forces at the time of injury leading to shear strain of the lenticulostriate or anterior choroidal vessels. 1,4,10,13,14-16 Based on the diameter, TBGH are classified as small (<2 cm) and large hemorrhages (>2 cm).…”
Section: Discussionmentioning
confidence: 99%